Collaboration in students' learning: the student experience. Issue 3 (8th October 2019) - Gratton, Rob
Abstract : Recognising that traditional approaches to education, and in turn a teaching and learning pedagogy which focus on the triumvirate of predefined knowledge, situationally applied understanding and domain specific skills were no longer appropriate, in 2009 I embarked upon an exploration of the myriad effects of an engagement with a pedagogy designed to facilitate Collaborative Group Learning (CGL) within a History classroom in a North London Secondary School. Following an identification of the recorded benefits of collaborative learning, I sought to isolate the principles of collaborative group learning, apply these principles to classroom practices of both the educator and learner and over a period of twenty‐four weeks capture and narrate the benefits of actively engaging in CGL. Central to the narrative were the experiences and perceptions of the thirty Year 8 boys (aged 12‐13 years) who experienced CGL over a period of twenty‐four weeks. The study identified a range of benefits of engaging in and with this form of inclusive pedagogy including, effective self‐directed and autonomous learning, interdependence, enhanced verbal communication skills and social‐cohesion. An unintended outcome has also been academic success measured through progress and attainment.